RESEARCH AND APPLICATION OF DIGITAL SIGNATURES IN E-COMMERCE TODAY - Thoi, Nguyen Thi (The journal of contemporary issues in business and government, 2021)
Nowaday, the digital age is expanding with the strong development of 4.0 Industry. The transformations of the flat world force businesses to have solutions to handle their works quicker, safer, more efficient, convenient and with high security so that they can trade goods. Declare tax, contracting, etc. all data are digitized in order to be easily stored, retrieved and accessed. To resolve the mentioned problems, the research topic "Researches and applications of digital signatures in Nowaday E-commerce" will explain what digital signature is, the application of digital signature (tokens) in e-commerce, hence, provides methods and goals to users, creates premises for higher development in Information Technology.